Repetition of accidents in young children. - Eminson, C; Jones, H; Goldacre, M (1986)
Data from the Oxford Record Linkage Study have been used to describe rates of accident repetition for children aged under 5 years. As reflected by hospital admissions, accident rates for children who have already had one accident were approximately twice those of children of the same age and sex who had previously been accident free.